ASSESSMENT OF NUTRITIONAL STATUS AMONG AOLESCENTS GIRLS - Phukan, Bani Lekha (International Journal of Psychosocial Rehabilitation, 2020)
Adolescence is the most important period of child’s life, in girls it begins with the onset of puberty. Nutrition needs receive adequate attention in bringing up adolescents. The nutritional status indicates both immediate and long range effects. When left unchecked it might enter into the genetics and affects the secular trend. Recognizing adolescent girls as high risk group, initiating intervention programmes for implementing their nutrition are essential for achieving success in breaking the cycle of malnutrition and improving their health. The purpose of this study is to assess the nutritional status of the selected adolescent girls. A questionnaire - based survey was conducted among 100 female students of the age group of 17–19 years. To assess their nutritional awareness a questionnaire was developed which included aspects such as dietary consumption pattern and consumption of snacks, foods eaten outside. The nutritional status of the selected sample was assessed through anthropometric measurement, dietary intake by 24 hours recall method and biochemical estimation. The study revealed that majority of the adolescent girls was conscious about nutritional status. When they were asked about the maintenance of nutritional status, 40 per cent mentioned healthy life and 28 per cent mentioned eating nutritious food, keeping the body healthy and proper hard work were the other ways of maintaining nutritional status as mentioned by each of 16 per cent which shows that the sample did not have any awareness on maintenance of their nutritional status. Nutrition education can help the adolescents to know better about the nutritional aspects of foods, their functions and need for good nutrition during this stage